MENJADIKAN PEMILIH PEREMPUAN KOTA SEMARANG YANG CERDAS MEMILIH DALAM PEMILU SERENTAK 2019 - Fitriyah Fitriyah; Puji Astuti; Dewi Erowati; Nunik Retno Herawati; Priyatno Harsasto (Sekolah Vokasi Universitas Diponegoro, 2020)
The 2019 general election was the first simultaneous election, besides the voter turnout of Semarang City in the last election did not reach the KPU RI's target of 77.5%. This election socialization program was to increase the quantity and quality of voter turnout. The number of women voters in the City of Semarang is greater than men, so women are the target group. This program chose